Analisis Perubahan Undang-Undang Ketenagakerjaan Terhadap Undang Undang Cipta Kerja Klaster Perjanjian Kerja Waktu Tertentu (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The implementation of the Job Creation Law (UU Job Creation) in Indonesia presents significant changes in employment regulations, especially regarding Specific Time Work Agreements (PKWT). This article evaluates the impact of the Job Creation Law on PKWT by analyzing changes in legal provisions that affect worker characteristics, rights and protection. The Job Creation Law introduces flexibility during the PKWT period, providing leeway for entrepreneurs to adapt working conditions to their business needs. However, this also raises concerns regarding the protection of workers' rights in certain time-based employment relationships. Efforts to clarify wage standards, benefits and social protection for workers in PKWT are the main highlight of this change. The importance of strict monitoring of the implementation of the Job Creation Law in the PKWT is crucial to ensure a balance between the interests of employers and workers' rights. Discussion and collaboration between the government, trade unions, employers and other stakeholders are essential to formulate fair and sustainable regulations for workers and equitable economic growth.